2002
DOI: 10.1002/j.2161-007x.2002.tb00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual and Religious Competencies: A National Survey of CACREP‐Accredited Programs

Abstract: In this study of 94 Counsel for Accreditation of Counseling and Related Educational Programs (CACREP)-accredited counselor education programs, 69% of respondents reported their programs addressed spiritual and religious issues; however, only 46% of CACREP liaisons perceived themselves as preparedor verypreparedto integrate material related to spirituality and religion in counseling into their teaching and supervision activities. In addition, only 28% of respondents viewed their colleagues as similarly capable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 18 publications
(25 reference statements)
6
107
0
3
Order By: Relevance
“…In fact only 21% felt that these issues had been addressed in their training program. When this data is compared with the study done by Young et al (2002), which found that 69% of CACREP accredited programs said that they addressed spiritual and religious issues in training, an interesting inconsistency emerges. It may be that many programs address religion and spirituality in an elective or as part of a course on multiculturalism.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In fact only 21% felt that these issues had been addressed in their training program. When this data is compared with the study done by Young et al (2002), which found that 69% of CACREP accredited programs said that they addressed spiritual and religious issues in training, an interesting inconsistency emerges. It may be that many programs address religion and spirituality in an elective or as part of a course on multiculturalism.…”
Section: Discussionmentioning
confidence: 88%
“…Recognition of the potentially powerful nature of a client's religious or spiritual beliefs and how when incorporated into counseling may readily facilitate change is a potent line of research (Young et al, 2002). In fact, Kelly (1995) in his book titled Spirituality and Religion in Counseling and Psychotherapy: Diversity in Theory and Practice summarized a Gallup poll, which suggests that when faced with a serious problem, the majority of people would prefer to see a counselor who holds spiritual values or beliefs.…”
Section: Counseling Literature On Spirituality Religion and Valuesmentioning
confidence: 99%
“…55 We don't need to reinvest the wheel where quality efforts have already been made in other areas of research and clinical focus. If we follow this template and caution, Professor Bergin's 1980 call for integrating and reflecting on religious and spiritual values as appropriate and professional aspects of psychotherapy will be realized.…”
Section: Next Steps Moving Forwardmentioning
confidence: 99%
“…For instance, Young et al [58] found that only 23 of 94 counseling programs accredited by Council for Accreditation of Counseling and Related Educational Programs (CACREP) offer only one specific course on spirituality and religion in counseling. Furthermore, content analysis of syllabi for spirituality courses showed inclusion of religion/spirituality in the curriculum was addressed in limited detail [59].…”
Section: Cultural Competence and Psychotherapymentioning
confidence: 99%